GLOBECOM 2017 - 2017 IEEE Global Communications Conference 2017
DOI: 10.1109/glocom.2017.8255036
|View full text |Cite
|
Sign up to set email alerts
|

User Presence Estimation in Multi-Occupancy Rooms Using Plug-Load Meters and PIR Sensors

Abstract: In the built environment, the paradigm is shifting from providing uniform environment for all occupants to accommodating individual preferences through decentralised comfort devices enabled by IoT (Internet of Things) and ubiquitous computing. The effective implementation of localised and personalised comfort-enhancing and energy-saving strategies depends critically on the ability to detect the occupant presence in the immediate local environment. In this paper, estimating individual user presence in a shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Other research has addressed occupancy inference in offices with extensive measurement units (i.e., one power meter per device) [10], [11]. Shetty et al observed the presence of four workers by monitoring the consumption of monitor screens and PCs, any by using a PIR sensor in each workplace [10]. To assign presence and absence states, they performed a kmeans clustering analysis on the measurement data.…”
Section: ) Room and Workpace Occupancymentioning
confidence: 99%
See 2 more Smart Citations
“…Other research has addressed occupancy inference in offices with extensive measurement units (i.e., one power meter per device) [10], [11]. Shetty et al observed the presence of four workers by monitoring the consumption of monitor screens and PCs, any by using a PIR sensor in each workplace [10]. To assign presence and absence states, they performed a kmeans clustering analysis on the measurement data.…”
Section: ) Room and Workpace Occupancymentioning
confidence: 99%
“…The authors reported that .90 accuracy and .69 Kappa could be reached using their proposed approach. Shetty et al reported .94 averaged accuracy of three people, but they failed to detect the absence states of another person [10].…”
Section: B Occupancy Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have studied the occupancy detection in offices by mining power consumption. Yet, they mostly utilize intrusive power meter, either per appliance or per work desk, as clustered in the top right of Figure 2 They employ a clustering approach of PIR sensor data and the power consumption of a PC and monitor during one-week observation [119]. Similarly, Zhao et al deploy power meter per appliance in more varied appliances, including fans, chargers, lights, and printers [139].…”
Section: Power Monitoringmentioning
confidence: 99%
“…In a cubicle office environment, binary occupancy detection has been approached by deploying power meters for each computer-related device (e.g., PCs and monitors) and a PIR sensor in each workspace [119]. Unsupervised k-means clustering is applied to interpret the absent and present state for each of four users.…”
Section: Power Consumption Data Miningmentioning
confidence: 99%